Coherent random lasing from nano-scale aggregates of hybrid molecules by enhanced near zone scattering. Issue 88 (8th September 2016) - Yin, Leicheng; Liang, Yunyun; Yu, Bo; Wu, Yeping; Ma, Jiajun; Xie, Kang; Zhang, Wei; Zou, Gang; Hu, Zhijia; Zhang, Qijin
Abstract : Random laser boosted by chemical bond linked active scatterer based on aggregation enhanced near zone scattering. Abstract : Nano-scale aggregates of hybrid molecules, such as N, N ′-di-[3-(isobutyl polyhedral oligomeric silsesquioxanes)propyl] perylene diimide (DPP) which is composed of perylene diimide (PDI) as gain group and polyhedral oligomeric silsesquioxanes (POSS) as scattering group at a mole ratio of 1 : 2, are formed in carbon disulfide (CS2 ) solution within a concentration range from 3 × 10 −5 M to 10 −3 M. The aggregation of DPP in the solution was characterized using ultraviolet visible (UV-vis) and fluorescence spectroscopy. Under pumping of a 532 nm pulse laser, coherent random laser (RL) is produced from the aggregates in CS2 solution with a threshold of 17.4 μJ and a Q value of 2440 at a DPP concentration of 10 −4 M. Enhanced near zone scattering by aggregation is thought to boost coherent RL. This research not only extends the RL system to the extremely weak scattering regime but also provides a new direction for research on nano-scale materials for lasers using molecular design.